Audit of geomagnetic field in polar and south atlantic anomaly regions over two centuries - Kakad, Amar; Kakad, Bharati (My University, 2022)
There are several reports about the decrease of the magnetic field of our planet. Here, we present a detailed investigation of the geomagnetic field over past 200 years using magnetic field models (IGRF+gufm1) and ground magnetic field observations until 2020. There are two prominent regions of consistently decreasing geomagnetic field namely: the South Atlantic Anomaly (SAA) and the southern pole region. The SAA region with field decreasing at 30 nT/year drifting to the south-west, whereas, the southern pole region with field decreasing at the rate 13 nT/year steadily drifting to the north-west. The Earth’s polar (66_–90_) magnetic field was invariably higher around the south pole as compared to the field around the north pole. However, it is found that over the past few decades (since 1950), the average magnetic field in the southern polar region has decreased to such an extent that presently it is weaker than the northern polar magnetic field. This tendency of cross-over in the magnitudes of average polar magnetic field strength is also evident in the ground magnetic field observations. On the ground at Hermanus (station in the SAA region), the rate of decrease of the magnetic field is found to be much higher (98 nT/year) during 1950–2020. Such a significant decrease in the magnetic field at Hermanus could be associated with the splitting of the SAA as it is situated close to the second minima in the SAA region. It is found that the magnetic field gradients around the center of the SAA become shallower as we move towards the higher altitudes. Also, the center of the SAA steadily moves in the north-east direction with increasing altitude. Though the weakening of the geomagnetic field is not an impulsive phenomenon but can invoke serious concerns to our life, satellites, and climate in near future.
Keywords: Geomagnetic field; South atlantic anomaly; Polar geomagnetic field; Satellite and climate; Audit